Constipation in Children with Cerebral Palsy: Prevalence, Clinical Manifestations, and Polyethylene glycol vs. Lactulose Efficacy: Constipation with cerebral palsy and polyethylene glycol combination with lactulose - Sadeghvand, Shahram; Taghizadeh Orangi, Ali; Mansouripour, Sophia; Golshan Shali, Erfan; Shoaran, Maryam; Erabi, Gisou; Fazeli Danesh, Sara (Iranian Journal of Child Neurology, 2025)
Objectives Cerebral palsy (CP) is a neurological disorder causing impaired movement control. Constipation is a common issue among these patients, with the prevalence ranging from 26% to 74%. This study aims to investigate the prevalence of constipation, examine associated symptoms, and compare the effects of commonly used drugs, including Lactulose and Polyethylene Glycol (PEG), in children with CP. These drugs can improve constipation management in this population and prevent serious complications, such as intestinal obstruction and bleeding. Materials & Methods: The present research was a prospective cross-sectional study of 48 children and adolescents aged 1 to 15 with CP. According to our definition of constipation based on the ROME IV criteria, the prevalence of constipation in children with CP was calculated. Patients were randomly divided into two groups: Group 1 received treatment with PEG, while Group 2 received treatment with Lactulose. The patients were followed up one month later and then every three months to assess treatment response and monitor clinical symptoms. Results: At both 12 and 24 weeks following the initiation of the treatment, a significant increase in the frequency of defecation per week was observed, accompanied by a notable decrease in the frequency of fecal incontinence in both groups. After 24 weeks of treatment, the defecation frequency increased from 1.5 to 6.3 in Group 1 (PEG group) and 1.6 to 5.7 in Group 2 (Lactulose group). Fecal incontinence reduced from initial values of 1.8 and 1.9 to 1.2 and 1.5 in Groups 1 and 2, respectively. Conclusion: This study confirms that constipation is a common problem among children with CP. According to the obtained findings, PEG appeared to be more effective than Lactulose in managing constipation in children with CP.